Interstitial Lung Disease and Psoriasis in a Child With Aicardi-Goutières Syndrome - Zheng, Shaoling; Lee, Pui Y.; Wang, Jun; Wang, Shihao; Huang, Qidang; Huang, Yukai; Liu, Yuqi; Zhou, Qing; Li, Tianwang (Frontiers in Immunology, 2020)
Aicardi-Goutières syndrome (AGS) is characterized by progressive neurologic decline, cerebral calcification and variable manifestations of autoimmunity. Seven subtypes of AGS have been defined and aberrant activation of the type I interferon system is a common theme among these conditions. We describe a 13-year-old boy who presented with an unusual constellation of psoriasis, interstitial lung disease (ILD) and pulmonary hypertension in addition to cerebral calcifications and glomerulonephritis. He was found to have late-onset AGS due to a gain-of-function mutation in IFIH1 and over-activation of the type I interferon pathway was confirmed by RNA sequencing. The majority of his clinical manifestations, including ILD, psoriasis and renal disease improved markedly after treatment with a combination of corticosteroids, cyclophosphamide and the Janus-kinase inhibitor tofacitinib. This case extends the clinical spectrum of AGS and suggests the need for lung disease screening in patients with AGS.